Eugenio Coseriu Beyond Structuralism - Kabatek, Johannes (De Gruyter, 2023)
Eugenio Coseriu (1921-2002) was among the most influential linguists in the second half of the 20th century. Although known mainly as a structuralist and an expert in Romance linguistics, his work in fact goes far beyond this, offering an impressive and coherent vision of linguistic theory that embraces a very wide range of issues. These are presented and discussed here in the first comprehensive monograph on Coseriu's œuvre published in English.